Desert locust swarm invasions and control: Determinants, duration, food security and effectiveness of control measures - Barasa, Benard; Walyalula Watsusi, Cosmas; Makoba Gudoyi, Paul; Lutaaya, Noah; Akello, Gertrude (Elsevier Inc., 2022)
Migratory desert locusts are partly to blame for chronic food insecurity in semi-arid areas. However, insufficient risk information is available on locust determinants, duration, survival rates and impacts on food security, but also on effectiveness of reactive control measures. The data analysed included household survey (2020), MODIS Soil-Adjusted-Vegetation-Index (SAVI) and Climate-Hazards-Group-Infrared-Precipitation with Station-data (CHIRPS) of 2018-2020. Findings showed that the roaring swarms were determined by vegetation health, strong winds and soil type (P<=0.05). The invasions lasted for 3 to 4 weeks, however, 90% of locusts survived beyond one week. The ecosystems that favoured them included woodlands, wetlands, thickets/shrubs, grasslands and farmlands. The greenness of vegetation is an important parameter in the attraction of locusts. They fed on the green tree structure (leaves, nodes, shoots). Most swarm invasions occurred during the rainy season. Overall, the invasions reduced crop and livestock yields. After the attacks, most households depended on food purchases for atleast four months. The most effective control measures implemented were ground and aerial pesticide spraying of locusts that killed them along their life-cycle. It is therefore, important to strengthen locust surveillance and use of chemicals in the management of locusts, but also strengthen disaster legal and institutional systems.
Keywords: Desert locusts; Survival; Locust control; Food security; Uganda